Synergity Analysis of Advance Organizer and Project Based Learning Models with Improvements Sociology Learning Outcomes of High School Students - Abednego Abednego (International Journal of Education, Information Technology, and Others, 2021)
Abstract. This study analyzed the synergy of the AO and PBL models in constructing students' cognitive, affective and psychomotor structures. The objective to find out whether there is a significant effect of the synergy AO and PBL model on high school sociology learning outcomes. According to the characteristics of quantitative research methods using True Experimental Design with Pretest-Posttest Only Control Design. In this study, there were two groups selected at random. The experimental group was the treatment synergy group of the AO and PBL models, while the control group was the group that used the PBL model, each group consisting of 23 students. Material structure, lesson plans, pre-test and post-test learning outcomes, as well as observation are used as research data collection instruments. The data were analyzed using the N-Gain Test for the experimental group and the control group, after the Normality Test and Homogeneity Test were carried out. The last paired sample T-test was conducted. Research findings revealed 1) The average N-Gain score for the experimental group is 91.9 or 91.9% (Effective) compared to the average N-Gain score for the control group which is 67.89 or 67.8% (Effective enough). 2) The results of the Paired Sample T-Test concluded that there was a significant influence between the experimental group and the control group on the learning outcomes of sociology in high school. It is recommended that the synergy of the AO and PBL models can be implemented in education and teaching activities in high school.